Makna Tradisi Tingkeban Dalam Upacara Manusa Yadnya Sebagai Fungsi Etnopedagogik di Desa Kalirejo, Kendal, Jawa Tengah - Ni Nyoman Sudiani; I Wayan Saklit; Risnia Kusmiani (Jurnal Penelitian Agama Hindu, 2026)
The Tingkeban tradition is an important ritual in Javanese culture, performed when a pregnancy enters the seventh month. Within the framework of Hindu teachings, Tingkeban can be understood as part of the Manusa Yadnya ceremony, a sacred sacrifice intended for human welfare and honoring new life. Although the tradition seems ancient, Hinduism has not abandoned tradition because tradition or culture is created through mind. Every culture contains values ​​that are beneficial to humanity, but in the modern era, belief in them has faded. Therefore, the values ​​​​in the Tingkeban tradition that is carried out to this day are important to reveal through research. This study aims to uncover the meaning behind the Tingkeban tradition practiced by Javanese Hindus, including the form, meaning, and function of the Tingkeban tradition in Kalirejo Village, Kendal, Central Java. This research is a qualitative study, data collected in the field through interviews, observation, and documentation. The results reveal that each element, both in rituals and offerings, contains spiritual, social, and philosophical meanings that reflect the harmonious relationship between humans, nature, ancestors, and God. The Tingkeban tradition also has a strong social function, including strengthening social relations, fostering a spirit of mutual cooperation, and serving as an ethnopedagogical medium for passing on cultural values ​​to the younger generation. Amidst the rapid flow of modernization, the people of Kalirejo Village continue to maintain this tradition as a cultural identity and community identity, as well as a form of local wisdom that is still alive and relevant to today's society. The conclusion is that the Tingkeban tradition contains noble values ​​that are worth maintaining until now because through this ritual, pregnant women are psychologically calmed which has an impact on fetal development.